Assessment on Disaster Risk Reduction of Tropical Storm Washi - Olavo Rasquinho (Tropical Cyclone Research and Review, 2013)
ABSTRACT: In December, 2011, the world's second most deadly disaster of the year, Tropical Storm Washi (known as Sendong in the Philippines) landed along the east coast of Mindanao, Philippines, causing 1,292 deaths, 1,049 missing, 2,002 injured, and total 695,195 people (110,806 families) affected. This paper introduced briefly the hydro-meteorological characteristics of Washi, and assessed its devastating impacts on society and economy, and the response and recovery taken by the Philippines government during the whole period of Washi. Based on the assessment of impact of disaster, the paper indicated the gaps and needs on aspects of DRR actions and identified the future challenges on typhoon related disaster preparedness and reduction in the Philippines. Finally, the report provided the recommendations within the framework of the activities of Typhoon Committee to improve and enhance the capacity building on typhoon related disaster reduction in the Philippines. Keywords: disaster risk reduction, tropical cyclones, Washi, assessment